2005
DOI: 10.1016/s0210-4806(05)73378-7
|View full text |Cite
|
Sign up to set email alerts
|

¿Es necesaria la orquidectomía en los pacientes con testículo no descendido post-puberal?

Abstract: In the following up of the patients none of them presented contralateral testicle cancer between 5-10 years. The patients who were practiced the orchiopexy no-one presented testicular cancer between 5-11 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…One of the testes was found to have a malignancy consisting of a pure seminoma. In the subsequent follow-up period, none of the patients in either group (orchiopexy or orchiectomy) developed a malignancy in the contralateral testis [ 23 ].…”
Section: Treatment Of Postpubertal Cryptorchidismmentioning
confidence: 99%
“…One of the testes was found to have a malignancy consisting of a pure seminoma. In the subsequent follow-up period, none of the patients in either group (orchiopexy or orchiectomy) developed a malignancy in the contralateral testis [ 23 ].…”
Section: Treatment Of Postpubertal Cryptorchidismmentioning
confidence: 99%
“…Furthermore, 5% of all testicular cancers are associated with cryptorchidism. Granados Loarca and Esau Ortega [ 8 ] reported that one of the 25 (4%) postpubertal undescended testis patients they assessed had seminoma, and similarly, Ben Jeddou et al [ 9 ] found that two of 81 patients aged >14 years with undescended testis had malignant disease. In the present study, one of the 34 men with untreated postpubertal undescended testis was diagnosed as having ITGCN.…”
Section: Discussionmentioning
confidence: 99%